Design of the robotic self-travelling sprinkler system - Ozaki, Yuriko (Cranfield University, 1999)
A conventional rain gun system is adversely affected by windy conditions. Therefore, the robotic self-travelling sprinkler (STS) system that controls the head and the water supply with relation to instant windy conditions. The robotic STS head has two degrees of freedom; sector and trajectory angles, driven by stepper motors to follow the control model, which are found by applying prediction models of water distribution, Centre of volume and Semi-empirical models. As a result, it was shown that the control for the sector angle compensated for the horizontal water distortion from wind, however, the trajectory angle was found to need more data to model the optimum trajectory angle. To control the water supply, a cut-off solenoid valve was installed and shut when wind was over 6 m/s upwind and 7 m/s downwind. This indicated that the trajectory angle was less than 10 degrees above horizontal. Under such windy conditions, water can not be distributed as far from the STS as required or becomes spray, which cannot reach to the ground. As the experimental results showed, the system enabled to minimize the commercially ineffective water distribution. A chemigation system was added, which can injects chemicals into the main water flow. The system enables farmers to save the cost for extra chemigation equipment. The process of the system while working can be checked by the interactive communication system between the embedded computer and the user’s computer. Therefore, this system made the robotic STS system more reliable, furthermore, it enabled the user’s computer to read and save the data sent from the field controller unit. This robotic STS system can distribute water or chemicals to the required area, even if up to the irregular boundaries,(fence lines, comers of fields), with the minimum water supply. Also, the system is ready to incorporate treatment maps and DGPS. In other words, it is possible to feed the adequate amount of water or chemicals which varies depending on the different regions of fields, species of plants, and seasons.